Certificateless searchable public key encryption scheme for mobile healthcare system. (January 2018) - Ma, Mimi; He, Debiao; Khan, Muhammad Khurram; Chen, Jianhua
Highlights: A new certificateless public key encryption with keyword search for mobile healthcare system is proposed. The security analysis of the proposed scheme shows our scheme can resist chosen keyword attack under two types of adversaries. The performance analysis shows the proposed scheme has lower computation cost and lower communication cost, in comparison with other scheme. Abstract: As mobile communication technology develops, mobile healthcare system (MHS) is becoming a hot topic in academia and healthcare industry. MHS refers to providing medical services through mobile communication equipments. However, it faces many challenges, such as the finite storage, computing power and communication capabilities of MHS devices. To address this problem, the concept of cloud-based MHS has been proposed recently. Meanwhile, healthcare data outsourcing to cloud raises privacy and confidentiality concerns. In order to protect data security, we present an efficient certificateless public key encryption with keyword search (CLPEKS). Security analysis indicates that our scheme is secure resist chosen keyword and keyword guessing attacks in random oracle model. The computation costs of KeyGen, CLPEKS, Trapdoor and Test phases decreased by 84.68%, 55.04%, 36.1% and 28.73%, respectively, compared with Peng et al.'s scheme.